A Descriptive Study On Teaching Vocabulary Using Game Of Observation And Memorization At The Fourth Year Of Sdn 2 Sendang Wonogiri - Tyani., Shevy Ari; , Drs. Djoko Srijono, M. Hum; , Mauly Halwat Hikmat, Ph. D (2014)
This descriptive research is aimed at describing teaching-learning vocabulary at the fourth year of SDN 2 Sendang Wonogiri using game of observation and memorization. The problem in this research focuses on the process of theaching vocabulary, then the problems faced by the teacher and the problems solving by the teacher. Game is tools that make it easier for the children to learn new things. Children will be interested in learning English vocabulary if the learning game is fun. The child will want to play the game and learn without thinking about learning. The writer takes the fourth grade students as the subject of the research. The data are taken from observation in the classroom and interview with the English teacher. There are seven steps in classroom activity. The steps consist of opening the class, explanation, consultation, practice, presentation, evaluation, and clossing. Based on the research finding, it can be concluded that the problem faced by the teacher in teaching vocabulary are different motivation and ability of the students. The problem solving applied by teacher in teaching vocabulary is creating a good relationship between the teacher and students. The teacher is giving advices and motivations about their importance learning vocabulary early. The teacher collaborates the teaching-learning process with game and must be calm to teach one by one from easy material.The use of game can increase the students' motivation and interest in studying new vocabulary.